The Production Process of Lithics in Late Bronze Age at Shahrake Firouzeh Site in Neyshabur, North East of Iran. (3rd December 2018) - Rezaei, Mohammad Hossein; Basafa, Hassan
Nowadays, the study of lithics has gained a special status in prehistoric archaeology and even archaeology of later periods. Shahrake Firouzeh is one of the most important prehistoric settlements ever detected in Neyshabur Plain in Khorasan Razavi Province. In general, based on the past excavation seasons, Shahrake Firouzeh site represents the Bronze Age and probably Iron Age cultures in the region and the bulk of cultural materials indicates a culture known as BMAC (Bactria-Margiana Archaeological Complex). This paper analyzes the typology of Shahrake Firouzeh lithics, which is a key typical site related to Late Bronze Age in Northeast of Iran. The collection of stone artifacts from Shahrake Firouzeh excavations includes 66 pieces. These tools have been recovered from nine trenches in different parts of the site during four excavation seasons, all of which belong to Late Bronze Age. The majority of lithics in this site are of debitage type. In addition to producing sickle blades bearing signs of sickle gloss, the main feature of this collection is production of arrowheads retouched in two sides. It should be noted that all the stone artifacts from Shahrake Firouzeh have been made from high quality chert stone in a color range of cream, honey, and transparent with semi-glossy surface. In general, the raw material used is of good quality, although it does not seem to have large dimensions. The raw material source is unknown, and thus no data can be presented on usage patterns of raw material.